Blood Biomarkers and 6- to 7-Year Childhood Outcomes Following Neonatal Encephalopathy - Pappas, Athina; Shankaran, Seetha; McDonald, Scott A.; Carlo, Waldemar A.; Laptook, Abbot R.; Tyson, Jon E.; Das, Abhik; Skogstrand, Kristin; Hougaard, David M.; Higgins, Rosemary D. (American Journal of Perinatology, 2020)
Objective This study aimed to profile the cytokine/chemokine response from day 0 to 7 in infants (≥36 weeks of gestational age) with neonatal encephalopathy (NE) and to explore the association with long-term outcomes.Study Design This was a secondary study of the Eunice Kennedy Shriver National Institute of Child Health and Human Development (NICHD) Neonatal Research Network randomized controlled trial of whole body hypothermia for NE. Eligible infants with moderate–severe NE were randomized to cooling or normothermia. Blood spots were collected on days 0 to 1, 2 to 4, and 6 to 7. Twenty-four cytokines/chemokines were measured using a multiplex platform. Surviving infants underwent neurodevelopmental assessment at 6 to 7 years. Primary outcome was death or moderate–severe impairment defined by any of the following: intelligence quotient <70, moderate–severe cerebral palsy (CP), blindness, hearing impairment, or epilepsy.Results Cytokine blood spots were collected from 109 participants. In total 99 of 109 (91%) were assessed at 6 to 7 years; 54 of 99 (55%) developed death/impairment. Neonates who died or were impaired had lower early regulated upon activation normal T cell expressed and secreted (RANTES) and higher day 7 monocyte chemotactic protein (MCP)-1 levels than neonates who survived without impairment. Though TNF-α levels had no association with death/impairment, higher day 0 to 1 levels were observed among neonates who died/developed CP. On multiple regression analysis adjusted for center, treatment group, sex, race, and level of hypoxic ischemic encephalopathy, higher RANTES was inversely associated with death/impairment (odds ratio (OR): 0.31, 95% confidence interval [CI]: 0.13–0.74), while day seven MCP-1 level was directly associated with death/impairment (OR: 3.70, 95% CI: 1.42–9.61). Targeted cytokine/chemokine levels demonstrated little variation with hypothermia treatment.Conclusion RANTES and MCP-1 levels in the first week of life may provide potential targets for future therapies among neonates with encephalopathy.Key Points
Keywords: hypoxic-ischemic encephalopathy; neuro-developmental impairment; blood biomarkers; cytokines; chemokines; RANTES; MCP-1